An Original Way to Investigate Silver Migration Through Silicon Carbide Coating in TRISO Particles. Issue 6 (14th March 2014) - Geng, Xin; Yang, Fan; Rohbeck, Nadia; Xiao, Ping; Vance, L.
<x xml:space="preserve">Abstract</x> Extensive release of the metastable silver nuclide Ag110m from fully intact tristructural‐isotropic (TRISO) particles raises concerns over safety of advanced nuclear reactors. In this study, we propose a new model to interpret the silver migration mechanism in SiC based on experimental observations from both Ag/SiC composite pellets and TRISO particles with an entrapped silver layer. For the Ag/SiC composite pellets heat treated at 1450°C, silicon was detected in the silver phase, amorphous carbon was found, and new β‐SiC had formed at the Ag/SiC interface. The results indicate that Ag in its liquid state reacts with SiC by forming a Ag–Si alloy. Carbon precipitates as a second phase or reacts with the Ag–Si alloy to form new SiC. Results from the heat‐treated TRISO particles trapping Ag show that Ag penetrates through the SiC layer and is present in either "finger‐shape" or "wedge shape" at the SiC grain boundaries. Ag was also found inside abnormally large SiC grains at the trailing edge between Ag and SiC, indicating the recrystallization of SiC. A dissolution‐reaction model was proposed to explain Ag migration through SiC, and this model is supported by thermodynamic calculations.